Land Dispute Resolution: Village Deliberation and Consensus to Establish Public Order - Gunawan, Yoga; Dialog, Bias Lintang; Fitriana, Diana (Unifikasi : Jurnal Ilmu Hukum, 2023)
Land disputes are common in society, and the village head, as witnessed by the family, resolved the matter in congruence with the parties' will and good intention. Purpose: to investigate the arrangement of land dispute resolution in Indonesia and to investigate its application through consensus deliberation in villages to realise public order. Methodology: a socio-legal approach involving primary data gathered from the interview. Furthermore, the study was also conducted in Kuningan Regency. Findings in Indonesia, land dispute resolution has been completely regulated, ranging from laws to derivative regulations, and is carried out through community discourse and consensus. However, the deliberation method is more common than going to court. The deliberations include bringing the parties together; if peace arrangements can be made, they will be made. It can, however, only function optimally if both sides (the family and the community) agree to deliberate. The method is thought to be more efficient in terms of time, cost, and mechanism.  Conclusion: In the village, there are two procedures for resolving land conflicts through consensus deliberation: mediation and family negotiation. Recommendation at the village level, it is critical to provide a legal framework for deliberation so that the outcomes are more equitable and mutually beneficial to all parties.